Laparoscopic Redo-Pyeloplasty Using Vertical Flap Technique - Nouralizadeh, Akbar; Lashay, Alireza; Radfar, Mohammad Hadi (Urology Journal, 2014)
Laparoscopic Redo-Pyeloplasty Using Vertical Flap Technique